An Ecological Perspective of Food Choice and Eating Autonomy Among Adolescents - Ziegler, Amanda M.; Kasprzak, Christina M.; Mansouri, Tegan H.; Gregory, Arturo M.; Barich, Rachel A.; Hatzinger, Lori A.; Leone, Lucia A.; Temple, Jennifer L. (Frontiers in Psychology, 2021)
Adolescence is an important developmental period marked by a transition from primarily parental-controlled eating to self-directed and peer-influenced eating. During this period, adolescents gain autonomy over their individual food choices and eating behavior in general. While parent-feeding practices have been shown to influence eating behaviors in children, little is known about how these relationships track across adolescent development as autonomy expands. The purpose of this qualitative study was to identify factors that impact food decisions and eating autonomy among adolescents. Using the food choice process model as a guide, four focus groups were conducted with thirty-five adolescents. Focus group discussion was semi-structured, asking teens about influences on their food choices across different food environments, their involvement with food purchasing and preparation, and perceived control over food their choices. Focus group transcripts were analyzed using deductive and inductive code creation and thematic analysis. This study found six leading influences on adolescents’ food choices and identified additional factors with prominence within specific environmental contexts. This study distinguished a broader spectrum of factors influencing adolescent food choice that extend beyond ‘convenience’ and ‘taste’ which have previously been identified as significant contributors. The degree of control that teens reported differed by eating location, occasion, and social context. Finally, adolescents demonstrated various levels of engagement in behaviors related to their eating autonomy. Identifying the emergent themes related to adolescent autonomy was the first step toward the goal of developing a scale to evaluate adolescent eating autonomy.